Incidence of and factors associated with perioperative cardiac arrest within 24 hours of anesthesia for emergency surgery - Visith Siriphuwanun (2018)
© 2014 Siriphuwanun et al. Patients and methods: This retrospective cohort study was approved by the ethical committee of Maharaj Nakorn Chiang Mai Hospital, Thailand. We reviewed the data of 44,339 patients receiving anesthesia for emergency surgery during the period from January 1, 2003 to March 31, 2011. The data included patient characteristics, surgical procedures, American Society of Anesthesiologists (ASA) physical status classification, anesthesia information, location of anesthesia performed, and outcomes. Data of patients who had received topical anesthesia or monitoring anesthesia care were excluded. Factors associated with cardiac arrest were identified by univariate analyses. Multiple regressions for the risk ratio (RR) and 95% confidence intervals (CI) were used to determine the strength of factors associated with cardiac arrest. A forward stepwise algorithm was chosen at a P-value ,0.05. Results: The incidence (within 24 hours) of perioperative cardiac arrest in patients receiving anesthesia for emergency surgery was 163 per 10,000. Factors associated with 24-hour perioperative cardiac arrest in emergency surgery were age of 2 years or younger (RR =1.46, CI =1.03-2.08, P=0.036), ASA physical status classification of 3-4 (RR =5.84, CI =4.20-8.12, P,0.001) and 5-6 (RR =33.98, CI =23.09-49.98, P,0.001), the anatomic site of surgery (upper intra-abdominal, RR =2.67, CI =2.14-3.33, P,0.001; intracranial, RR =1.74, CI =1.35-2.25, P,0.001; intrathoracic, RR =2.35, CI =1.70-3.24, P,0.001; cardiac, RR =3.61, CI =2.60-4.99, P,0.001; and major vascular; RR =3.05, CI =2.22-4.18, P,0.001), respiratory or cardiovascular comorbidities (RR =1.95, CI =1.60-2.38, P,0.001 and RR =1.38, CI =1.11-1.72, P=0.004, respectively), and patients in shock prior to receiving anesthesia (RR =2.62, CI =2.07-3.33, P,0.001). Conclusion: The perioperative incidence of cardiac arrest within 24 hours of anesthesia for emergency surgery was high and associated with multiple factors such as young age (≤2 years old), cardiovascular and respiratory comorbidities, increasing ASA physical status classification, preoperative shock, and surgery site. Perioperative care providers, including surgeons, anesthesiologists, and nurses, should be prepared to manage promptly this high risk group of surgical patients. Purpose: To determine the incidence of and factors associated with perioperative cardiac arrest within 24 hours of receiving anesthesia for emergency surgery.